Safety of Irreversible Electroporation Ablation of the Pancreas. Issue 9 (3rd October 2021) - Lee, Edward Wolfgang; Shahrouki, Puja; Peterson, Stephanie; Tafti, Bashir A.; Ding, Peng-Xu; Kee, Stephen T.
Abstract : Objectives: To evaluate the safety of irreversible electroporation (IRE) on swine pancreatic tissue including its effects on peripancreatic vessels, bile ducts, and bowel. Methods: Eighteen Yorkshire pigs underwent IRE ablation of the pancreas successfully and without clinical complications. Contrast-enhanced computed tomography angiography and laboratory studies before the IRE ablation with follow-up computed tomography angiography, laboratory testing, and pathological examination up to 4 weeks postablation were performed. Results: In a subset of cases, anatomic peripancreatic vessel narrowing was seen by 1 week postablation, persisting at 4 weeks postablation, without apparent functional impairment of blood flow. Laboratory studies revealed elevated amylase and lipase at 24 hours post-IRE, suggestive of acute pancreatitis, which normalized by 4 weeks post-IRE. There was extensive pancreatic tissue damage 24 hours after IRE with infiltration of immune cells, which was gradually replaced by fibrotic tissue. Ductal regeneration without loss of pancreatic acinar tissue and glandular function was observed at 1 and 4 weeks postablation. Conclusions: In our study, we demonstrated and confirmed the safety and minimal complications of IRE ablation in the pancreas and its surrounding vital structures. These results show the potential of IRE as an alternative treatment modality in patients with pancreatic cancer, especially those with locally advanced disease.